International Labor Migration, Economic Growth and Labor Markets - The Current State of Affairs - Christoph M. Schmidt; John P. Haisken-DeNew; Thomas K. Bauer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2004)
Even though European labor markets are characterized by high average unemployment, there is a shortage of high-skilled labor, leading many European economists to argue for an immigration policy directed at actively recruiting highly qualified workers from abroad. It has further been argued that an immigration policy that is tailored to attract young and economically successful migrants can alleviate some of the demographic burden associated with an aging population.We embed this discussion into a systematic classification of economic migration research according to its major conceptual and applied questions. The state of theoretical and empirical research on the migration decision, the literature on the economic performance of immigrants and their economic impact is reviewed briefly, proceeding along the lines of a clear conceptual framework. In addition, the paper discusses expectations on future migration flows and the policy options of immigration countries for dealing with these flows.
Keywords: F22; J61; 330; Immigration; European labor markets; Immigration policy; Internationale Arbeitsmobilität; Einwanderung; Arbeitsmarkt; Wirtschaftswachstum; Theorie; EU-Staaten